Embryonic and Larval Development of Thai Pangas Pangasianodon Hypopthalmus (Sauvage, 1878) Under Hatchery Condition (Bangladesh Journal of Zoology, 2021)
The embryonic and larval development of Pangasianodon hypophthalmus was investigated during peak spawning periods (May-July 2019). The fertilized eggs were adhesive and spherical with a greenish‐brown egg capsule. The yolk sac was yellowish‐brown in color and 1.00–1.70 mm in diameter. The first cleavage stage, embryonic shield, head, tail region, neural grooves and somites were apparent after fourteen hours post‐fertilization. The ranges of incubation period were from 18.00-20.00 hrs at a temperature of 26-30°C. The newly hatched larvae were transparent and light yellowish in color with a body length of 2.98–3.10 mm. Eye pigment appeared and the heart started to work within 12-16 hrs of hatching. The mouth became well developed at the age of 24 hrs; barbules were prominent, elongated and look like threads. The yolk sac was fully absorbed and the palatine teeth were fully increased during the 3 days pro‐larval stage. The stomach became functional and aerial respiration started after 3 days of larval development. After 72 hrs, the young fry was well‐developed, and appeared an adult, and length was measured up to 7.20±0.02 mm. When daily ration of pangas larvae is insufficient cannibalism was recorded. This study must be supportive for researcher and nursery owner on the biology and ecology of the fish, which might be helpful for appropriate measure of sustainable nursery, rearing and management technology of pangas.Bangladesh J. Zool. 49(1): 147-159, 2021